2016
DOI: 10.1515/hsz-2016-0104
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-544 down-regulates both Bcl6 and Stat3 to inhibit tumor growth of human triple negative breast cancer

Abstract: Triple negative breast cancer lacking estrogen receptor (ER), progesterone receptor and Her2 account for account for the majority of the breast cancer deaths, due to the lack of specific gene targeted therapy. Our current study aimed to investigate the role of miR-544 in triple negative breast cancer. Endogenous levels of miR-544 were significantly lower in breast cancer cell lines than in human breast non-tumorigenic and mammary epithelial cell lines. We found that miR-544 directly targeted the 3'-untranslate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…MiR‐544 has been reported to be dysregulated in several cancers. For example, miR‐544 can inhibit human triple negative breast cancer development by inhibiting Bcl6 and STAT3 (Zhu et al, ). miR‐544 is able to restrain the epithelial‐to‐mesenchymal transition (EMT) through targeting the TWIST1 in in carcinoma patients (Haga & Phinney, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR‐544 has been reported to be dysregulated in several cancers. For example, miR‐544 can inhibit human triple negative breast cancer development by inhibiting Bcl6 and STAT3 (Zhu et al, ). miR‐544 is able to restrain the epithelial‐to‐mesenchymal transition (EMT) through targeting the TWIST1 in in carcinoma patients (Haga & Phinney, ).…”
Section: Discussionmentioning
confidence: 99%
“…Error bars stand for the mean ± SD of at least triplicate experiments. *p < 0.05, **p < 0.01 development by inhibiting Bcl6 and STAT3(Zhu et al, 2016). miR-544…”
mentioning
confidence: 97%
“…Based on the miRNA target predication software, we initially predicted miRNA targets of the top 5 upregulated and validated circRNAs and then subjected them to down-regulated MPE-associated miRNAs, indicating up-regulated circRNAs might inhibit the expression of down-regulated miRNAs. Among the 23 potential miRNAs, some have been reported as important regulaters in many kinds of cancers [42][43][44][45][46][47][48]. For example, L Bao et al revealed that downregulation of miR-298 increased P-Glycoprotein expression and induced doxorubicin resistance in sensitive breast cancer cells, suggesting miR-298 was associated with the chemoresistant mechanisms of metastatic human breast cancer by directly modulating P-Glycoprotein expression [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-6 or HIF-1A-induce STAT3 and InH3 expression, resulting in the induction of invasion and metastasis of CRC by repression of miR-34a [205]. Moreover, miR-216 inhibits the activation of JAK2/STAT3 signaling by reducing JAK2 expression [206], and miR-544 suppresses the expression of both Bcl6 and STAT3 by direct targeting [207]. Furthermore, miR-26a inhibits metastasis through the downregulation of IL-6 expression by reducing the expression of Lin-28 homolog B (LIN28B), HMGA1, and MITF as a direct target and through the restoration of LIN28B-reduced let7d expression [208,209].…”
Section: Micrornas As Negative Regulatorsmentioning
confidence: 99%